“Ganpati Bappa Morya!” Lo spazio del sacro migrante nella festa di Ganesh a Palermo - Eugenio Giorgianni (Archivio Antropologico Mediterraneo)
This article examines through a participative approach the Ganesha festival and how it helps migrant people of Mauritian origin in Palermo in the process of place-making by mediating between the city and the migrant community. The Ganpati celebrates the Mauritian devotees’ spatial and social mobility, connecting them to their affective transnational networks through social media. The devotional community reacted to the policy responses to COVID-19 by enhancing the domestic aspects of the festival, preserving the core meaning of the rite. The festival takes place through a relational network involving the whole community thanks to women’s collective solidarity. On the other hand, the ritual prestige creates competition and elicits the group’s internal fractures and intersections. Hindu devotional spaces are created by re-functionalizing marginal segments of the city and provoke ambivalent reactions from the rest of the citizens.